Hematological and Biochemical Reference Intervals for Mules in Chile - Lagos, Javiera; Tadich, Tamara A. (Frontiers in Veterinary Science, 2019)
Hematological and biochemical reference intervals are an important tool for health assessment and treatment decision-making in veterinary medicine. Lack of information about reference intervals in mules force professionals to apply reference intervals developed for horses or donkeys, with the risk of misinterpretation. Thus, the aim of this study was to determine hematological and biochemical reference intervals for healthy mules and compare them with those proposed in literature for horses, donkeys and mules. A total of 142 healthy mules were sampled and 32 blood parameters analyzed in order to calculate reference intervals according to the International Federation of Clinical Chemistry Clinical (IFCC) and the Clinical Laboratory Standards Institute (CLSI) standards. The reference intervals obtained for Chilean mules showed poor overlapping with UK donkeys and working horses in Pakistan, and no similarities with those from Portuguese mules. A limited overlap was found with Chilean working horses values. The differences found in blood biochemistry can be explained by husbandry conditions, diet, type of work and biological features. Differences between mules reference intervals and those from donkeys and working horses highlight the importance of having specific reference values for this equid hybrid and the need to develop further research in mules under different working conditions and genetic background.